Sequential measurement of Trypanosoma cruzi parasitic load in endomyocardial biopsies for early detection and follow‐up of Chagas disease reactivation after heart transplantation. Issue 1 (21st November 2019) - Benvenuti, Luiz Alberto; Roggério, Alessandra; Nishiya, Anna Shoko; Mangini, Sandrigo; Levi, José Eduardo
Abstract: Background: Reactivation of Chagas disease after heart transplantation is characterized by proliferation and dissemination of Trypanosoma cruzi parasites to several organs. Reactivation affecting the allograft can simulate acute cellular rejection, from which it should be distinguished through the analysis of endomyocardial biopsies (EMB). Methods: We evaluated retrospectively 100 EMB collected in the first year of follow‐up from 13 heart‐transplanted, chagasic patients who presented reactivation and were successfully treated. Additionally, 37 EMB from 8 patients who did not present reactivation constituted the control group. We reviewed histopathology and performed a real‐time PCR‐based assay in order to evaluate the T cruzi parasitic load of each EMB. Results: The parasitic load of the EMB at the time of reactivation ranged from 22.80 to 190 000/10 6 cells (median: 1555). In 6 patients, none of the EMB obtained prior to reactivation amplified T cruzi DNA. On the other hand, 10 EMB from 7 patients, obtained 9‐105 days before reactivation (median: 26 days), showed parasitic load ranging from 8.25 to 625/10 6 cells (median: 167.55). In all patients, the parasitic load increased at the time of reactivation, usually sharply. After initiation of treatment, all patients showed negative PCR or a dramatic reduction of the parasitic load in the following EMB. None of the EMB from the control group amplified T cruzi DNA. Conclusions: Sequential measurement of T cruzi parasitic load in EMB is useful for monitoring Chagas disease reactivation after heart transplantation. Its increase suggests imminent reactivation and its decrease after treatment indicates favorable evolution for cure of the episode of reactivation.